3-boyutlu lorentz uzayında modified sabban çatılarına göre slant helisler - Baykara, Kübra Bulut (Fırat Üniveristesi, 2026)
Bu çalışmanın amacı, Lorentz uzayında 𝑆12 ve 𝐻02 üzerinde Sabban çatılarının ve modified Sabban çatılarının slant helis olmaları için gerekli ve yeterli şartları veren yeni karakterizasyonları ifade etmek ve ispat etmektir. Anahtar Kelimeler: Sabban Çatı, Modified Sabban çatı, Slant helis

The aim of this study is to express and prove novel characterizations that provide the necessary and sufficient conditions for Sabban frame and modified Sabban frame to be slant helices on 𝑆12 and 𝐻02 in Lorentz space. Keywords: Sabban frame, Modified Sabban Frame, Slant Helice
Slant helices with respect to modified sabban frames in 3-dimensional lorentz space
Keywords: Matematik